Cone Beam Computed Tomography Analysis of Three Method of Intracanal Calcium Hydroxide Placement - Naomi Ranjan Singh1 , Siba Prasad Jena1 , Lora Mishra2, Debkant Jena2 ,Sumit Dash2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim: To compare and evaluate the quality of three different method of intracanal placement of calciumhydroxide paste through CBCT.Methodology: Thirty single-rooted mandibular premolars were decoronated and cleaning and shaping wasdone using Protaper Rotary Files(till F4). The canals were divided into the following three groups whichwere filled with a radiopaque calcium hydroxide paste based on three insertion method (n = 10, each): usinga Master Gutta-percha cone (MGP), Pastinject (PIT), and a technique combining conventional hand fileswith ultrasonic activation(UST). The quality of fillings was assessed using CBCT by examining the numberof canal walls coated dividing the root into thirds. Statistical analysis was done using the Chi-square test ofindependence.Results: The canals filled with combined technique (hand files with ultrasonic activation) had a better coatingof canal walls followed by Master GP cone and Pastinject, with significant differences between them.Conclusion: From the images obtained through CBCT analysis, calcium hydroxide placed utilizing handfiles with ultrasonic activation (UST) produced better coating of canal walls over Master GP and Pastinjecttechniques.